Conformational Itinerary of Sucrose During Hydrolysis by Retaining Amylosucrase - Alonso-Gil, Santiago; Coines, Joan; André, Isabelle; Rovira, Carme (Frontiers in Chemistry, 2019)
By means of QM(DFT)/MM metadynamics we have unravelled the hydrolytic reaction mechanism of Neisseria polysaccharea amylosucrase (NpAS), a member of GH13 family. Our results provide an atomistic picture of the active site reorganization along the catalytic double-displacement reaction, clarifying whether the glycosyl-enzyme reaction intermediate features an α-glucosyl unit in an undistorted 4C1 conformation, as inferred from structural studies, or a distorted 1S3-like conformation, as expected from mechanistic analysis of glycoside hydrolases (GHs). We show that, even though the first step of the reaction (glycosylation) results in a 4C1 conformation, the α-glucosyl unit undergoes an easy conformational change towards a distorted conformation as the active site preorganizes for the forthcoming reaction step (deglycosylation), in which an acceptor molecule, i.e. a water molecule for the hydrolytic reaction, performs a nucleophilic attack on the anomeric carbon. The two conformations (4C1 ad E3) can be viewed as two different states of the glycosyl-enzyme intermediate (GEI), but only the E3 state is preactivated for catalysis. These results are consistent with the general conformational itinerary observed for α-glucosidases.